2008
DOI: 10.1080/14756360701654894
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hydroxybenzyl alcohols on melanogenesis in melanocyte-keratinocyte co-culture and monolayer culture of melanocytes

Abstract: In mammalian skin, melanocyte proliferation and melanogenesis can be stimulated by keratinocytes, fibroblasts and other regulatory factors. To determine whether hydroxybenzyl alcohols (HBAs) show more inhibitory in melanocytes cultured alone or in melanocytes co-cultured with keratinocytes, we developed a murine melanocyte -keratinocyte co-culture model to investigate the pigmentation regulators in company with other melanogenic inhibitors and stimulators. It was found that the effects of HBAs and melanogenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Consistent with the in vitro study, 1.25 mg/cm 2 and 2.5 mg/cm 2 LSE treatments suppressed melanogenesis by inhibiting PKA and p38 activation. Earlier studies have shown that the melanin production in melanocytes is influenced by keratinocytes and fibroblasts [30,31]. Primary melanocytes and keratinocytes have some drawbacks such as the limited proliferation capacity and the donor variability [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with the in vitro study, 1.25 mg/cm 2 and 2.5 mg/cm 2 LSE treatments suppressed melanogenesis by inhibiting PKA and p38 activation. Earlier studies have shown that the melanin production in melanocytes is influenced by keratinocytes and fibroblasts [30,31]. Primary melanocytes and keratinocytes have some drawbacks such as the limited proliferation capacity and the donor variability [31].…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have shown that the melanin production in melanocytes is influenced by keratinocytes and fibroblasts [30,31]. Primary melanocytes and keratinocytes have some drawbacks such as the limited proliferation capacity and the donor variability [31]. Primary murine melanocytes defective at the Mc1r locus have been historically difficult to culture in vitro [32].…”
Section: Discussionmentioning
confidence: 99%
“…0.5 × 10 4 melanocytes : 5 × 10 4 keratinocytes) in the mixed medium and incubated at 37°C, 5% CO 2 . The initial seeding ratio of melanocytes to keratinocytes used a 1:10 ratio according to the previous study 5 . We mixed the culture media with various concentration ratios (1:1, 1:2, 1:5 and 1:10) of advanced iDMM to keratinocyte growth medium, respectively.…”
Section: Figurementioning
confidence: 99%
“…Monolayer models are useful for studying melanocyte properties and testing different conditions or drugs. In 2008, in a comparative study of melanocytes culture and melanocytes-keratinocytes co-culture, Liu et al demonstrated the effect of melanogenic stimulators (α-MSH and L-tyrosine) and inhibitors (arbutin and hydroxybenzyl alcohols (HBA)) in the two conditions [113]. Results showed that α-MSH and L-tyrosine increased the melanin content of melanocytes, and that the increase was better in the co-culture with keratinocytes.…”
Section: Monolayersmentioning
confidence: 99%